Comparing Labor Market Trajectories of Refugee Women to Other Immigrant and Native-Born Women in the United States. Issue 4 (1st October 2020) - Vijaya, Ramya
ABSTRACT: Even as the world has witnessed an unprecedented number of displaced individuals, resettlement of refugees has been met with fears about their ability to integrate into host economies. Such fears are compounded by the limited information on the long-term economic outcomes of resettlement. This study uses American Community Survey data to explore the labor market integration of refugee women resettled in the United States over the period 2002–16. It finds that, over time, refugee women tend to surpass the labor force participation (LFP) rates of native-born and other immigrant women in the US even after controlling for individual characteristics like level of education, English proficiency, and home country LFP. This indicates that refugee women are able to adapt and make positive contributions to the host labor market and strengthens the case for expanded refugee-resettlement programs in developed economies. HIGHLIGHTS The charged political debate in many developed economies about integrating refugees into economic and cultural life is often based on unfounded stereotypes. Gendered labor market outcomes of resettled groups are important to investigate since these outcomes have influenced other immigrant groups' assimilation experiences. Though resettled refugee women in the US start with lower labor force participation rates than other groups, they outpace other immigrant and native-born women over time. Refugee women's labor force participation rates are not influenced by their home country participation rates. Refugee women, therefore, seem quick to adapt to host country labor markets. However, their wages remain lower indicating structural inequality rather than lack of assimilation.